Significance of Whey protein concentrate and Calcium caseinate on shelf-life study and textural profiles of dahi - Hati, Subrota; Patel, Rekha (Indian Journal of Dairy Science, 2017)
Dahi was prepared using optimized 1% WPC 70 or 2% Ca-caseinate by L. helveticus MTCC 5463 (V3) culture. These products were evaluated for storage stability at refrigeration temperature (7±2°C). Sensory attributes of 1% WPC or 2% Ca-caseinate supplemented dahi were analyzed upto 15 days at intervals of 5 days under refrigeration temperature. Dahi supplemented with WPC 70 had improved the sensory scores for flavour, body & texture, acidity, colour & appearance and overall acceptability as compared to control and Ca-caseinate supplemented dahi. All of these products were analyzed for textural profiles during refrigerated storage (7±2°C) for 15 days. Dahi prepared with Ca-caseinate showed highest hardness, fracturability, gumminess, adhesiveness & chewiness while WPC 70 supplemented sample exhibited highest cohesiveness, resilience & springiness as compared to control.